(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we define V-fuzzy b-metric space and by using concept of a set-valued or multi-valued quasi-contraction mapping a fixed point theorem is established.MSC: primary 47H10; secondary 54H25.